Preparation method and application of lithium-sulfur battery positive electrode material

By adding morphological regulators and graphene oxide to the preparation of the positive electrode material of lithium sulfur battery, a graphene oxide-laden heterojunction composite material is formed, which solves the problem of low performance of lithium sulfur batteries and achieves higher specific capacity and better cycle stability.

CN119841351AActive Publication Date: 2025-04-18SHANDONG HAIHUA GRP CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510315317.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The active substances of lithium-sulfur batteries have poor conductivity, and the reaction kinetic speed is reduced, resulting in a reduction in battery performance; there will be a shuttle effect when dissolved in the electrolyte, causing the dissolution of the active substance and the retention rate to decrease; the volume changes of the positive electrode material during the charging and discharge process cause the electrode material to fall off and collapse in structure.

Method used

When preparing the positive electrode material of lithium sulfur battery, morphology regulators and graphene oxide are added to form graphene oxide-supported heterobond composite material, which changes the morphology of the material, increases the active site, and solves the volume expansion problem through the coating of graphene oxide.

Benefits of technology

The electrochemical performance of lithium-sulfur batteries is improved, the specific capacity and cycle stability are improved, and the capacity retention rate remains at 77-84% after cycling for 300 cycles at 1C current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841351A_ABST
    Figure CN119841351A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a lithium-sulfur battery positive electrode material, and belongs to the technical field of lithium-sulfur battery positive electrode materials. The preparation method comprises the following steps: adding ammonium tetrathiomolybdate into N, N-dimethylformamide to form a uniform mixed solution, carrying out a reaction in a closed container, and after the reaction is finished, carrying out suction filtration, cleaning and drying to obtain molybdenum disulfide powder; and sequentially dissolving a bismuth salt and a molybdenum salt in a dilute solution of an inorganic strong acid, adding an amine morphology regulating agent into the dilute solution, carrying out a reaction, sequentially adding the obtained molybdenum disulfide powder and graphene oxide to obtain a mixed solution, carrying out a reaction in a closed container, and carrying out freeze drying after the reaction is finished to obtain the lithium-sulfur battery positive electrode material. By adding the amine morphology regulating agent, the morphology of the material can be changed, more active sites are obtained, the problem of volume expansion is also solved by coating, and the electrochemical performance of the lithium-sulfur battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur battery positive electrode materials, and in particular relates to a preparation method and application of a lithium-sulfur battery positive electrode material. Background Art

[0002] Among the many new energy storage methods, electrochemical energy storage has the advantages of convenience, long life and low cost, and is widely used in life. In contrast, Li-S batteries with lithium metal as the negative electrode and sulfur (sulfur-containing materials) as the positive electrode have attracted a lot of attention. This is because Li-S batteries have extremely high theoretical discharge capacity (1672mAh / g) and theoretical energy density (2600Wh / kg), and are abundant in the earth's crust, low in price, and environmentally friendly.

[0003] However, the active materials sulfur and lithium sulfide of lithium-sulfur batteries have poor conductivity, and the reduced reaction kinetics cause the battery performance to decrease; polysulfides dissolve in the electrolyte and there will be a shuttle effect, causing the active materials to dissolve and the cycle retention rate to decrease; the volume change of the positive electrode material during the charge and discharge process is also an important reason for the detachment of the electrode material and the collapse of the structure.

[0004] The Chinese patent document with publication number CN106732667A discloses a method for preparing a graphene-like molybdenum disulfide-bismuth molybdate composite material by reducing a protein substance. First, intercalated molybdenum disulfide powder is obtained by intercalation reaction, then bismuth nitrate and sodium molybdate are dissolved in a solvent, and then intercalated molybdenum disulfide powder and protein are added to obtain a precursor material, and finally calcined to obtain a graphene-like molybdenum disulfide-bismuth molybdate composite material. This method requires controlling the amount and ratio of four solvents added in the intercalation reaction, and the process is relatively cumbersome. The SEM image shows that the composite material has an irregular morphology and a limited number of exposed active sites.

[0005] The Chinese patent document with publication number CN106582720A discloses a method for preparing a graphene-like molybdenum disulfide-bismuth molybdate composite material by reducing sugar organic carbon, firstly obtaining intercalated molybdenum disulfide powder by intercalation reaction, then dissolving bismuth nitrate and sodium molybdate in a solvent, then adding intercalated molybdenum disulfide powder and sugar organic carbon to obtain a precursor material, and finally calcining to obtain a graphene-like molybdenum disulfide-bismuth molybdate composite material. The composite material obtained by this method has an irregular structure and severe agglomeration, a limited number of active sites, and a weak response to electrochemical performance.

[0006] The Chinese patent document with publication number CN113206233A discloses a bismuth molybdate / sulfur composite material, its preparation method and lithium-sulfur battery. Soluble bismuth salt and molybdenum salt are dissolved in a solvent, and bismuth molybdate rich in oxygen vacancies is obtained by solvent thermal reaction. Bismuth molybdate is mixed with elemental sulfur and calcined to obtain a bismuth molybdate / sulfur composite material. The composite material synthesized by this method has enhanced adsorption capacity for lithium polysulfide and can inhibit the shuttle effect of the material. However, the capacity retention rate of the material is only 63-75% (0.05C, 250 cycles) due to volume expansion, and the cycle stability is poor under low current.

[0007] The Chinese patent document with publication number CN115621435A discloses a manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery cathode host material and its preparation method and application, with molybdenum disulfide nanosheets as the main body, and manganese sulfide nanoparticles anchored on molybdenum disulfide nanosheets to form a composite material with a manganese sulfide-molybdenum disulfide heterostructure. The composite material has a two-dimensional nanosheet structure, which is conducive to exposing more active sites and promoting electrolyte infiltration, but the cycle performance will decrease (71%, 0.5C 300 cycles) due to volume expansion during the cycle, and the stability is poor. Summary of the invention

[0008] The purpose of the present invention is to provide a preparation method and application of a lithium-sulfur battery positive electrode material. The morphology of the material can be changed by adding a morphology regulator to obtain more active sites. The coating also solves the volume expansion problem and can improve the electrochemical performance of the lithium-sulfur battery.

[0009] In order to achieve the purpose of the present invention, a technical solution for a preparation method of a positive electrode material for a lithium-sulfur battery is provided, comprising the following steps: (1) adding ammonium tetrathiomolybdate to N,N-dimethylformamide to form a uniform mixed solution, reacting in a first closed container, and filtering, washing, and drying after the reaction to obtain molybdenum disulfide powder; (2) dissolving a bismuth salt and a molybdenum salt in a dilute solution of an inorganic strong acid in sequence, adding an amine morphology regulator thereto for reaction, and then adding the molybdenum disulfide powder and graphene oxide obtained in step (1) in sequence to obtain a mixed solution, reacting the solution in a second closed container, and freeze-drying the solution after the reaction to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a positive electrode material for a lithium-sulfur battery.

[0010] Preferably, in step (1), the concentration of ammonium tetrathiomolybdate in N,N-dimethylformamide is 4-25 mM.

[0011] Preferably, in step (1), the reaction temperature in the first closed container is 160-200°C, and the reaction time is 14-24 h; the filtration is performed three times with methanol, the drying temperature is 80-120°C, and the drying time is 8-12 h.

[0012] Preferably, in step (2), the molar ratio of bismuth salt to molybdenum salt is 1-2:1, the bismuth salt is any one of bismuth nitrate, bismuth chloride or bismuth sulfate; the molybdenum salt is any one of sodium molybdate, ammonium molybdate or potassium molybdate; the dilute solution of inorganic strong acid is any one of nitric acid, hydrochloric acid or sulfuric acid solution, with a concentration of 0.5-1 M; the concentration of bismuth salt in acidic solvent is 16-50 mM.

[0013] Preferably, in step (2), the amine morphology regulator is any one of ethylenediamine, triethanolamine, dodecylamine, or aniline, and the molar ratio of the morphology regulator to the molybdenum salt is 0.01-0.1:1; the molar ratio of molybdenum disulfide to the molybdenum salt is 0.15-0.875:1; and the mass ratio of graphene oxide to the molybdenum salt is 0.04-0.5:1.

[0014] Preferably, in step (2), the reaction temperature in the second sealed container is 120-180°C, and the reaction time is 16-24 h; the freeze-drying temperature is -60~-40°C, and the freeze-drying time is 24-48 h.

[0015] The present invention also provides the application of the prepared lithium-sulfur battery positive electrode material, which is applied to lithium-sulfur batteries.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The technical solution of the method for preparing the positive electrode material of a lithium-sulfur battery provided by the present invention promotes the formation of a heterojunction by adopting an acidic solvent to react in a closed environment and inducing a morphology regulator to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate composite material with a certain hierarchical structure. The heterojunction can form more active sites during the charge and discharge process of the lithium-sulfur battery, thereby improving the battery performance.

[0017] 2. The technical solution of the method for preparing the positive electrode material of a lithium-sulfur battery provided by the present invention changes the morphology of the bismuth molybdate matrix by adding a morphology regulator, and obtains a heterojunction material with different morphologies after compounding with molybdenum disulfide. The exposed active sites further promote the adsorption and migration of carriers, thereby improving the electrochemical performance of the lithium-sulfur battery.

[0018] 3. The technical solution of the method for preparing the positive electrode material of a lithium-sulfur battery provided by the present invention obtains a rod-shaped heterojunction material with nanosheet wrinkles by adding graphene oxide. The formation of wrinkles enables ions in the electrolyte to adsorb and react with the material at different angles. The addition of graphene oxide wraps the heterojunction material, which can effectively control the material structure collapse and cycle performance degradation caused by volume expansion.

[0019] 4. The application of the prepared lithium-sulfur battery positive electrode material provided by the present invention, through the performance test of the assembled lithium-sulfur battery in the blue electric test system, the material has excellent specific capacity and good cycle stability. The capacity can reach 1125-1258 mAh / g at a current density of 0.2C, and after 300 cycles at a current density of 1C, the capacitance value is 77-84% of the initial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the SEM spectrum of the GO@MoS2-Bi2MoO6 material prepared in Example 1; Figure 2 XRD spectra of MoS2 and GO@MoS2-Bi2MoO6 materials prepared in Example 1; Figure 3 This is the pore size distribution diagram of the GO@MoS2-Bi2MoO6 material prepared in Example 1; Figure 4 It is the magnification diagram of the materials obtained in Example 1 and the comparative example; Figure 5 This is a curve of capacity retention and coulombic efficiency of the GO@MoS2-Bi2MoO6 material prepared in Example 1 after 300 cycles at a current density of 1C. DETAILED DESCRIPTION

[0021] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. Example 1

[0022] (1) 0.6 mmol of ammonium tetrathiomolybdate was added to 30 mL of N,N-dimethylformamide to form a uniform mixed solution, which was then transferred to a first sealed container and reacted at 180 °C for 24 h. After the reaction, the mixture was filtered three times with methanol to remove excess N,N-dimethylformamide, and dried at 100 °C for 12 h to obtain molybdenum disulfide powder. (2) 3 mmol of bismuth nitrate and 1.5 mmol of sodium molybdate were dissolved in 80 mL of 0.5 M nitric acid solution, 6 mL of dodecylamine was added thereto, and then 0.2 g of molybdenum disulfide powder and 0.05 g of graphene oxide were added in sequence to obtain a mixed solution, which was transferred to a second sealed container and reacted at 180 °C for 20 h. After the reaction was completed, the solution was freeze-dried at -50 °C for 36 h to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a lithium-sulfur battery positive electrode material. Example 2

[0023] (1) 0.4 mmol of ammonium tetrathiomolybdate was added to 25 mL of N,N-dimethylformamide to form a uniform mixed solution, which was then transferred to a first sealed container and reacted at 200 °C for 22 h. After the reaction, the mixture was filtered three times with methanol to remove excess N,N-dimethylformamide, and dried at 120 °C for 8 h to obtain molybdenum disulfide powder. (2) 3 mmol of bismuth chloride and 1.5 mmol of ammonium molybdate were dissolved in 60 mL of 0.5 M hydrochloric acid solution, 8 mL of ethylenediamine was added thereto, and then 0.25 g of molybdenum disulfide powder and 0.03 g of graphene oxide were added in sequence to obtain a mixed solution, which was transferred to a second sealed container and reacted at 160 °C for 22 h. After the reaction was completed, the solution was freeze-dried at -60 °C for 24 h to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a lithium-sulfur battery positive electrode material. Example 3

[0024] (1) 0.8 mmol of ammonium tetrathiomolybdate was added to 35 mL of N,N-dimethylformamide to form a uniform mixed solution, which was then transferred to a first sealed container and reacted at 160 °C for 24 h. After the reaction was completed, the mixture was filtered three times with methanol to remove excess N,N-dimethylformamide, and dried at 80 °C for 12 h to obtain molybdenum disulfide powder. (2) 1.5 mmol bismuth sulfate and 1.5 mmol potassium molybdate were dissolved in 40 mL 0.5 M sulfuric acid solution, 2 mL aniline was added, and 0.1 g molybdenum disulfide powder and 0.07 g graphene oxide were added in turn to obtain a mixed solution, which was transferred to a second sealed container and reacted at 140 °C for 24 h. After the reaction was completed, the solution was freeze-dried at -40 °C for 48 h to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a lithium-sulfur battery positive electrode material. Example 4

[0025] (1) 0.1 mmol of ammonium tetrathiomolybdate was added to 25 mL of N,N-dimethylformamide to form a uniform mixed solution, which was then transferred to a first sealed container and reacted at 180 °C for 20 h. After the reaction, the mixture was filtered three times with methanol to remove excess N,N-dimethylformamide, and dried at 100 °C for 8 h to obtain molybdenum disulfide powder. (2) 2 mmol of bismuth chloride and 1 mmol of sodium molybdate were dissolved in 60 mL of 0.75 M hydrochloric acid solution, 4 mL of triethanol was added thereto, and then 0.15 g of molybdenum disulfide powder and 0.01 g of graphene oxide were added in turn to obtain a mixed solution, which was transferred to a second sealed container and reacted at 120 °C for 24 h. After the reaction was completed, the solution was freeze-dried at -45 °C for 42 h to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a lithium-sulfur battery positive electrode material. Example 5

[0026] (1) 0.2 mmol of ammonium tetrathiomolybdate was added to 30 mL of N,N-dimethylformamide to form a uniform mixed solution, which was then transferred to a first sealed container and reacted at 200 °C for 14 h. After the reaction, the mixture was filtered three times with methanol to remove excess N,N-dimethylformamide, and dried at 100 °C for 10 h to obtain molybdenum disulfide powder. (2) 2 mmol of bismuth sulfate and 1 mmol of sodium molybdate were dissolved in 80 mL of 0.75 M sulfuric acid solution, 6 mL of dodecylamine was added, and 0.065 g of molybdenum disulfide powder and 0.09 g of graphene oxide were added in sequence to obtain a mixed solution, which was transferred to a second sealed container and reacted at 160 °C for 18 h. After the reaction was completed, the solution was freeze-dried at -55 °C for 30 h to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material. Example 6

[0027] (1) 0.9 mmol of ammonium tetrathiomolybdate was added to 35 mL of N,N-dimethylformamide to form a uniform mixed solution, which was then transferred to a first sealed container and reacted at 160 °C for 16 h. After the reaction was completed, the mixture was filtered three times with methanol to remove excess N,N-dimethylformamide, and dried at 120 °C for 12 h to obtain molybdenum disulfide powder. (2) 2 mmol of bismuth nitrate and 1 mmol of ammonium molybdate were dissolved in 40 mL of 1 M nitric acid solution, 8 mL of ethylenediamine was added thereto, and then 0.3 g of molybdenum disulfide powder and 0.1 g of graphene oxide were added in sequence to obtain a mixed solution, which was transferred to a second sealed container and reacted at 180 °C for 16 h. After the reaction was completed, the mixture was freeze-dried at -50 °C for 36 h to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a lithium-sulfur battery positive electrode material. Example 7

[0028] (1) Add 1 mmol of ammonium tetrathiomolybdate to 40 mL of N,N-dimethylformamide to form a uniform mixed solution, transfer it to a first closed container and react at 200 °C for 18 h. After the reaction, filter it three times with methanol to remove excess N,N-dimethylformamide, and dry it at 80 °C for 10 h to obtain molybdenum disulfide powder; (2) 1 mmol of bismuth nitrate and 1 mmol of potassium molybdate were dissolved in 60 mL of 1 M nitric acid solution, 10 mL of aniline was added thereto, and then 0.35 g of molybdenum disulfide powder and 0.05 g of graphene oxide were added in sequence to obtain a mixed solution, which was transferred to a second sealed container and reacted at 140 °C for 20 h. After the reaction was completed, the solution was freeze-dried at -60 °C for 24 h to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a lithium-sulfur battery positive electrode material. Comparative Example 1

[0029] In this comparative example, no morphology control agent and graphene oxide were added, and the other processes were consistent with those in Example 1. Comparative Example 2

[0030] In this comparative example, no morphology control agent was added, and the other processes were consistent with those in Example 1. Comparative Example 3

[0031] In this comparative example, graphene oxide was not added, and the other processes were consistent with those in Example 1. Comparative Example 4

[0032] In this comparative example, molybdenum disulfide is not added, that is, the operation of step (1) is not performed, and molybdenum disulfide is not added in step (2), and the other processes are consistent with those of Example 1. Comparative Example 5

[0033] In this comparative example, step (2) is not performed, that is, the material is the molybdenum disulfide synthesized in step (1), and the rest is the same as the process of Example 1. Comparative Example 6

[0034] In this comparative example, purchased molybdenum disulfide powder is used, and step (1) is not performed, that is, step (1) is not performed, and purchased molybdenum disulfide is added in step (2), and the rest of the process is consistent with that of Example 1.

[0035] The prepared lithium-sulfur battery positive electrode material is assembled into a battery for testing: The graphene oxide loaded molybdenum disulfide-bismuth molybdate heterojunction composite material and sulfur powder were weighed at a mass ratio of 3:7, subjected to high-energy vibration ball milling at a vibration frequency of 2000 r / min for 30 minutes, kept at 155° C. for 8 hours in an argon atmosphere, and cooled to obtain a sulfur-loaded composite material, i.e., an active material.

[0036] The electrode was prepared by scraping. The active material, acetylene black and PVDF were weighed in a mass ratio of 8:1:1, NMP was added and stirred into a viscous slurry, which was scraped onto aluminum foil. After drying, it was cut with a slicer to obtain a φ12 electrode sheet. The lithium-sulfur battery was assembled in a glove box and electrochemical testing was performed after standing for 2 to 4 hours.

[0037] This application uses the above-mentioned electrode sheet as the positive electrode, the negative electrode is metallic lithium, the diaphragm is Celegard diaphragm, the electrolyte is 1mol / L lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), ethylene glycol dimethyl ether DME and dioxolane DOL (volume ratio of 1:1) are used as solvents, and assembled into a CR2032 type lithium sulfur battery for electrochemical testing. Constant current charge and discharge curve (GCD) test conditions: voltage window 1.8-3.0V, current density 0.2C, 0.5C, 1C, 2C, 4C. The capacity retention rate is tested by cycling 300 cycles at a current density of 1C.

[0038] The properties of the electrode materials obtained from the examples and comparative examples are summarized in Table 1 below.

[0039]

[0040] Figure 1 This is the SEM spectrum of the GO@MoS2-Bi2MoO6 material in Example 1. After adding dodecylamine morphology regulator, a rod-shaped material with MoS2 nanosheet clusters epitaxially grown on the rod-shaped matrix Bi2MoO6 can be obtained. Depending on the different morphology regulators, composite materials with different structures will be obtained. Due to its large aspect ratio, the rod-shaped matrix can load more MoS2 nanosheets and absorb more electrolyte ions; after being coated with graphene oxide, the structural collapse caused by volume expansion during the cycle can be reduced.

[0041] Figure 2The XRD spectra of MoS2 and GO@MoS2-Bi2MoO6 materials prepared in Example 1 show that the MoS2 material shows strong diffraction peaks at 2θ=14.13°, 32.91°, and 35.97°, and the characteristic peaks and diffraction peaks at other angles correspond to the results of the MoS2 standard card, proving that the MoS2 material is successfully synthesized; from the XRD spectrum of the GO@MoS2-Bi2MoO6 material, it can be seen that the diffraction peaks of Bi2MoO6, MoS2, and GO correspond well to the standard card, indicating that the GO@MoS2-Bi2MoO6 composite material is successfully obtained.

[0042] Figure 3 This is the pore size distribution diagram of the GO@MoS2-Bi2MoO6 material prepared in Example 1. The pore size distribution of the material is mainly concentrated in the micropore and mesopore areas, with a small part in the macropore area. The composite material has a hierarchical porous structure. The presence of micropores can adsorb and store more ions; the mesopores are concentrated in 10-30nm, and combined with the presence of some macropores, they can contact with more electrolytes, improve the diffusion capacity of the electrolyte, and promote the rapid transmission of electrons and ions, which can effectively improve the battery charging and discharging performance.

[0043] Figure 4 and Figure 5 They are the rate diagram of GO@MoS2-Bi2MoO6 material in Example 1, the capacity retention rate and coulomb efficiency curve after 300 cycles at 1C current density, and the Figure 4 From Table 1, it can be found that the specific capacity of the material in Example 1 at a current density of 0.2C is 1481 mAh / g. As the current density increases, the specific capacity shows a trend of gradually decreasing. At a current density of 4C, the specific capacity is 1053 mAh / g, and the rate performance is 71.12%. Figure 4 It can be found from Table 1 that the specific capacity of the embodiment and the comparative example materials both show a gradually decreasing trend with the increase of current density. This is because as the current density increases, the ions in the electrolyte have no time to respond on the surface of the electrode material, that is, the polarization effect becomes larger, causing the specific capacity to gradually decrease. Figure 5 The test of Example 1 was carried out for 300 cycles at a current density of 1C, and the specific capacity was 84.65% of the initial capacity, with excellent cycle stability.

[0044] Through the data in Table 1, we can find that compared with the composite materials without adding morphology control agent or / and graphene oxide in Comparative Examples 1 to 3, the specific capacity of the GO@MoS2-Bi2MoO6 material in the embodiment is improved, and the capacity retention rate is also maintained at 77-84%. Compared with the materials that do not form heterojunctions in Comparative Examples 4 and 5, the formation of heterojunctions in the embodiments will form photogenerated electron-hole pairs, the ion transition energy in the electrochemical reaction process is reduced, and the electrochemical activity is improved, thereby showing the improvement of electrochemical performance. Comparative Example 6 uses purchased molybdenum disulfide as a raw material to synthesize heterojunction composite materials, and the specific capacity and cycle performance are not ideal. With the addition of morphology control agents, the different ductility of molybdenum disulfide nanosheets grown on the substrate can increase the adsorption sites and diffusion channels of the material and the electrolyte ions, thereby improving the electrochemical performance of lithium-sulfur batteries; coupled with the coating of graphene oxide on the outermost layer, the obtained GO@MoS2-Bi2MoO6 material can avoid the shedding of electrode materials and structural collapse caused by volume expansion during charging and discharging. The addition of dodecylamine can obtain a rod-shaped material with epitaxial growth of MoS2 nanosheet clusters on the rod-shaped matrix Bi2MoO6. Since the aspect ratio of the rod-shaped structure is large, more nanosheets can be loaded, which increases the specific surface area of ​​the composite material. It can be seen from Table 1 that when the amount of dodecylamine added is 6mL and the amount of graphene oxide added is 0.05g, the material exhibits the best performance. The above results show that GO@MoS2-Bi2MoO6 material has excellent electrochemical performance and cycle stability in lithium-sulfur batteries.

[0045] The technical features of the above-described embodiments can be combined arbitrarily. To make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above implementation case description can be used to help understand the principles and methods of the present invention. However, the above implementation case is not unique and should not be construed as a limitation of the present invention. At the same time, for those of ordinary skill in the art, according to the principles and methods of the present invention, flexible changes can be made in specific implementation methods and application scopes.

Claims

1. A method for preparing a positive electrode material for a lithium-sulfur battery, characterized in that: The following steps are involved: (1) adding ammonium tetrathiomolybdate to N,N-dimethylformamide to form a uniform mixed solution, reacting in a first closed container, and filtering, washing, and drying after the reaction to obtain molybdenum disulfide powder; (2) dissolving a bismuth salt and a molybdenum salt in a dilute solution of an inorganic strong acid in sequence, adding an amine morphology regulator thereto for reaction, and then adding the molybdenum disulfide powder and graphene oxide obtained in step (1) in sequence to obtain a mixed solution, reacting the solution in a second closed container, and freeze-drying the solution after the reaction to obtain a graphene oxide-loaded molybdenum disulfide-bismuth molybdate heterojunction composite material, i.e., a positive electrode material for a lithium-sulfur battery.

2. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: In the step (1), the concentration of ammonium tetrathiomolybdate in N,N-dimethylformamide is 4-25 mM.

3. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: In the step (1), the reaction temperature in the first closed container is 160-200°C, and the reaction time is 14-24h; the filtration is performed three times with methanol, the drying temperature is 80-120°C, and the drying time is 8-12h.

4. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: In the step (2), the molar ratio of the bismuth salt to the molybdenum salt is 1-2:1, the bismuth salt is any one of bismuth nitrate, bismuth chloride or bismuth sulfate; the molybdenum salt is any one of sodium molybdate, ammonium molybdate or potassium molybdate; the dilute solution of the inorganic strong acid is any one of nitric acid, hydrochloric acid or sulfuric acid solution, with a concentration of 0.5-1 M; and the concentration of the bismuth salt in the acidic solvent is 16-50 mM.

5. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: In the step (2), the amine morphology regulator is any one of ethylenediamine, triethanolamine, dodecylamine, or aniline, and the molar ratio of the morphology regulator to the molybdenum salt is 0.01-0.1:1; the molar ratio of molybdenum disulfide to the molybdenum salt is 0.15-0.875:1; and the mass ratio of graphene oxide to the molybdenum salt is 0.04-0.5:

1.

6. The method for preparing the positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: In the step (2), the reaction temperature in the second sealed container is 120-180°C, and the reaction time is 16-24 hours; the freeze-drying temperature is -60~-40°C, and the freeze-drying time is 24-48 hours.

7. An application of a lithium-sulfur battery positive electrode material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The lithium-sulfur battery positive electrode material is applied to lithium-sulfur batteries.

Citation Information

Patent Citations

  • Preparation method of graphene-like molybdenum disulfide / bismuth molybdate composite material by reducing protein substance

    CN106732667A

  • Bismuth molybdate / sulfur composite material, preparation method thereof and lithium-sulfur battery

    CN113206233A

  • Lithium-sulfur battery anode host material based on manganese sulfide-molybdenum disulfide heterojunction as well as preparation method and application of lithium-sulfur battery anode host material

    CN115621435A

  • Preparation method of layered MoS2-Bi2MoO6 nanocomposite

    CN105664975A

  • Method for preparing graphene-like molybdenum disulfide-ferroferric oxide composite material through reduction for proteic substances

    CN106564962A